Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Let f(x) = 4x - 1, h(x) = - X-3.
Find (f o h)(-5).


Sagot :

Answer:

(f o h)(-5)=-33

Step-by-step explanation:

Let f(x) = 4x - 1, h(x) = - X-3.

(f o h)=4(-x-3)-1

(f o h)=-4x-12-1

(f o h)=-4x-13

(f o h)(-5)=-4(-(-5))-13

(f o h)(-5)=-20-13

(f o h)(-5)=-33